2014
DOI: 10.1116/1.4878940
|View full text |Cite
|
Sign up to set email alerts
|

GaSb oxide thermal stability studied by dynamic-XPS

Abstract: The thermal decomposition of the native GaSb oxides is studied using time resolved x-ray photoelectron spectroscopy with a temperature resolution of better than 1 K. The expected transfer of oxygen from Sb-O to Ga-O before the eventual desorption of all oxides is observed. However, an initial reaction resulting in the reduction of Sb 2 O 3 along with the concurrent increase in both Ga 2 O 3 and Sb 2 O 4 is detected in the temperature range of 450-525 K. Using the relative changes in atomic concentrations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
4
9
0
1
Order By: Relevance
“…It is indeed reasonable that the amount of Ga-O bonds becomes maximized in the initial oxygen exposure because Ga-O formation is energetically much more favored than Sb-O. 15 Also, the recent investigation of the InSb oxidation indicates that the oxidation starts with substituting subsurface Sb by O. 22,23 This suggests that the first-layer Sb-Sb and Sb-Ga dimers are not disintegrated at the initial stage of oxygen exposure, which can explain the STM and LEED observations that the Â3 dimer-row structure appears on the surface also after a prolonged oxidation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is indeed reasonable that the amount of Ga-O bonds becomes maximized in the initial oxygen exposure because Ga-O formation is energetically much more favored than Sb-O. 15 Also, the recent investigation of the InSb oxidation indicates that the oxidation starts with substituting subsurface Sb by O. 22,23 This suggests that the first-layer Sb-Sb and Sb-Ga dimers are not disintegrated at the initial stage of oxygen exposure, which can explain the STM and LEED observations that the Â3 dimer-row structure appears on the surface also after a prolonged oxidation.…”
mentioning
confidence: 98%
“…2 Gallium antimonide (GaSb) has attracted an increasing interest as for the channel material of future MOS transistors, in particular, due to a superior mobility of holes in GaSb. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The GaSb oxidation at the insulator interfaces such as atomiclayer-deposited (ALD) Al 2 O 3 /GaSb and HfO 2 /GaSb has been found to cause various oxidation states of GaSb including Ga 2 O, Ga 2 O 3 , Sb 2 O 3 , and/or Sb 2 O 5 according to x-ray photoelectron spectroscopy (XPS) measurements. 10,18 By obtaining interrelationship between the interfacial chemistry from, for example, XPS measurements and capacitance-voltage (C-V) characterization of the same interfaces, the effects of the oxidation states on the electrical properties of the interfaces have been clarified: it is interesting that neither Ga 2 O 3 -nor Sb 2 O 3type interface phase is necessarily harmful to the electrical performance.…”
mentioning
confidence: 99%
“…6 During exposure to atmosphere, the GaSb surface readily forms a native oxide composed Ga 2 O 3 , Sb 2 O 4 , Sb 2 O 3 . [8][9][10][11][12] At temperatures above 200 C, additional elemental Sb is formed as a result of the reaction between Sb-oxide and the underlying GaSb surface, 11 which is assumed to have an adverse effect, since the Sb rich native oxide/GaSb interface suffers from high interface state density (D it ) leading to Fermi level pinning. 13 Recent first principle studies of HfO 2 /GaSb interfaces formed on Ga-terminated surfaces have suggested that gap states were absent at oxygen-rich interfaces without direct Sb-O bonds.…”
mentioning
confidence: 99%
“…Отжиг поверхности в сверхвысоком вакууме не позволяет удалить этот оксидный слой без потери стехиометрии кристалла [10,11]. В этой связи были предложены различные методы обработки водородной [12] и азотной плазмой [13].…”
Section: Introductionunclassified